Mengoptimalkan Kinerja melalui Disiplin Kerja, Budaya Organisasi, dan Kreativitas Pegawai - Hanafi, Abdul (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
In the competitive business era, optimizing employee performance is the key to success for every organization. Work discipline, organizational culture and employee creativity are factors that play an important role in achieving superior and sustainable performance. This research aims to investigate the relationship between work discipline, organizational culture, and employee creativity in optimizing performance. The research method used is quantitative research with data collection through questionnaires distributed to employees from various levels in the organization. Data analysis was carried out using statistical techniques to test the relationship between these variables. The research results show that there is a significant relationship between the level of work discipline, supportive organizational culture, employee creativity, and performance. These findings provide an important contribution to understanding how these factors interact to achieve optimal performance in an organizational context.